EFFECT OF REGIONAL TAX, REGIONAL RETRIBUTION, OTHER PAD SAH, DAU, DAK AND DBH TO CAPITAL SHOPPING WITH GRDP AS MODERATING VARIABLE IN REGENCY / CITY OF NORTH SUMATERA PROVINCE - Ningsih, Vera Siahaan (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to find out whether regional tax, regional retribution, other valid PAD (Regional  Generated  Revenues), DAU (Block Grant), DAK (Special Grant), and DBH (Fund Sharing) simultaneously and partially had significant influence on capital expenditure and to find out whether PDRB could moderate the correlation of regional tax, regional retribution, other valid PAD, DAU, DAK, and DBH with capital expenditure. The research used quantitative causal comparative method with secondary data. The population was 165 data obtained from actual budget report of 33 districts/towns in North Sumatera Province within 5 years, using saturated (census) sampling technique. The data were analyzed by using multiple linear regression analysis and residual test. The result of the analysis showed that regional tax, regional retribution, other valid PAD, DAU, DAK, and DBH simultaneously influenced capital expenditure. Partially, regional tax, other valid PAD, DAU, and DAK, had significant influence on capital expenditure. PDRB could not moderate the correlation of regional tax, regional retribution, other valid PAD, DAU, DAK, and DBH with capital expenditure.